High Uptake of 123I-metaiodobenzylguanidine Related to Olfactory Neuroblastoma Revealed by Single-photon Emission CT - Sasajima, Toshio; Kinouchi, Hiroyuki; Tomura, Noriaki; Watarai, Jiro; Mizoi, Kazuo (American Journal of Neuroradiology, 2000)
Summary: We studied a case of olfactory neuroblastoma by noting 123I-metaiodobenzylguanidine (MIBG) uptake revealed by single-photon emission CT (SPECT). MR imaging revealed an enhancing tumor extending from the left nasal cavity to the bilateral anterior frontal cranial fossae. SPECT revealed high 123I-MIBG uptake in the enhancing tumor. SPECT-revealed 123I-MIBG uptake appears to be clinically useful for distinguishing olfactory neuroblastomas from other tumors, especially suprasellar meningiomas.